Neuroprotective and Angiogenesis Effects of Levetiracetam Following Ischemic Stroke in Rats - Yao, Xiang; Yang, Wenping; Ren, Zhendong; Zhang, Haoran; Shi, Dafa; Li, Yanfei; Yu, Ziyang; Guo, Qiu; Yang, Guangwei; Gu, Yingjiang; Zhao, Hairong; Ren, Ke (Frontiers in Pharmacology, 2021)
Objective: The present study explored whether levetiracetam (LEV) could protect against experimental brain ischemia and enhance angiogenesis in rats and investigated the potential mechanisms in vivo and in vitro. Methods: The middle cerebral artery was occluded for 60 minutes to induce an middle cerebral artery occlusion (MCAO). The Morris water maze was used to measure cognitive ability. The rotation test was used to assess locomotor function. T2-weighted MRI was used to assesse infarct volume. The neuronal cells in the cortex area were stained with cresyl purple. The anti-inflammatory effects of LEV on microglia were observed by immunohistochemistry. Enzyme-linked immunosorbent assays (ELISA) were used to measure the production of pro-inflammatory cytokines. Western blotting was used to detect the levels of heat shock protein 70 (HSP70), vascular endothelial growth factor (VEGF), and hypoxia-inducible factor-1α (HIF-1α) protein in extracts from the ischemic cortex. Flow cytometry was used to observe the effect of LEV on neuronal cell apoptosis. Results: LEV treatment significantly increased the density of the surviving neurons in the cerebral cortex and reduced the infarct size (17.8±3.3% versus 12.9±1.4%, P < 0.01) after MCAO. Concurrently, the time required to reach the platform for LEV - treated rats was shorter than that in the saline group on days 11 after MCAO (P < 0.01). LEV treatment prolonged the rotarod retention time on days 14 after MCAO (84.5±6.7s versus 59.1±6.2s on days 14 compared with saline - treated groups, P < 0.01). It also suppressed the activation of microglia and inhibited TNF-α and Il-1β in the ischemic brain (135.6±5.2 pg/mL versus 255.3±12.5 pg/mL, 18.5±1.3 pg/mL versus 38.9±2.3 pg/mL on days 14 compared with saline - treated groups, P < 0.01). LEV treatment resulted in a significant increase in HIF-1α, VEGF, and HSP70 levels in extracts from the ischemic cerebral cortex. At the same time, LEV reduced neuron cytotoxicity and apoptosis induced by an ischemic stroke (P < 0.01). Conclusion: LEV treatment promoted angiogenesis and functional recovery after cerebral ischemia in rats. These effects seems to be mediated through anti-inflammatory and anti-apopototic activities as well as inducing the expression of HSP70, VEGF, and HIF- 1α.